The Frustration with Utilization: Why Have Improvements in Internal Phosphorus Utilization Efficiency in Crops Remained so Elusive? - Rose, Terry J.; Rose, Michael T.; Pariasca Tanaka, Juan; Heuer, Sigrid; Wissuwa, Matthias (Frontiers in Plant Science, 2011)
Despite the attention internal phosphorus utilization efficiency (PUE) of crops has received in the literature, little progress in breeding crop cultivars with high PUE has been made. Surprisingly few studies have specifically investigated PUE; instead, genotypic variation for PUE has been investigated in studies that concurrently assess phosphorus acquisition efficiency (PAE). We hypothesized that genotypic differences in PAE confound PUE rankings because genotypes with higher PAE suffer a lower degree of P stress, resulting in lower PUE. The hypothesis was tested by comparing soil-based screening with a novel technique whereby rice genotypes were grown in individual containers with a single dose of soluble P, to eliminate differences in P uptake among genotypes. Genotypic differences in PUE were apparent in root and shoot tissue using the nutrient solution technique, and PUE rankings showed no correlation with those from traditional soil-based screening. We conclude that PUE in soil-based screening systems is unavoidably linked with genotypic PAE, resulting in PUE rankings confounded by differences in P uptake. Only screening techniques assuring equal P uptake are suitable for the exploitation of genotypic variation for PUE.